3rd Nordic NJF Conference on Reindeer Husbandry Research – “Reindeer husbandry in a Globalizing North - resilience, adaptations and pathways for actions” - Birgitta Åhman; Eva Wiklund (Rangifer, 2017)
The Nordic Conference on Reindeer Husbandry Research 2017 was held from 29 to 31 May in Jukkasjärvi, Kriuna, Sweden, hosted by the Reindeer section of NJF (Nordic Association of Agricultural Scientists) in collaboration with the Nordic Centre of Excellence ReiGN - Reindeer husbandry in a Globalizing North – resilience, adaptations and pathways for actions. This was the third conference on reindeer husbandry research arranged within NJF.